Proceedings of the Twenty-Seventh Annual ACM-SIAM Symposium on Discrete Algorithms 2015
DOI: 10.1137/1.9781611974331.ch92
|View full text |Cite
|
Sign up to set email alerts
|

Kernelization via Sampling with Applications to Finding Matchings and Related Problems in Dynamic Graph Streams

Abstract: In this paper we present a simple but powerful subgraph sampling primitive that is applicable in a variety of computational models including dynamic graph streams (where the input graph is defined by a sequence of edge/hyperedge insertions and deletions) and distributed systems such as MapReduce. In the case of dynamic graph streams, we use this primitive to prove the following results: *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
132
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(147 citation statements)
references
References 35 publications
3
132
0
Order By: Relevance
“…Although G has a perfect matching, the subgraph between the first n/2 vertices of A and the last n/2 vertices of B has Ω(n 2 ) edges, and the algorithm is very likely to pick these edges in the matching. A result by Chitnis et al [3] shows that the maximum matching can be found in the streaming model with a memory of sizeÕ(k 2 ) where k is the cardinality of the maximum matching. Therefore, if µ(G) ≤ √ n, using their algorithm we can find the exact solution using a memory of sizeÕ(n).…”
Section: Preliminariesmentioning
confidence: 99%
“…Although G has a perfect matching, the subgraph between the first n/2 vertices of A and the last n/2 vertices of B has Ω(n 2 ) edges, and the algorithm is very likely to pick these edges in the matching. A result by Chitnis et al [3] shows that the maximum matching can be found in the streaming model with a memory of sizeÕ(k 2 ) where k is the cardinality of the maximum matching. Therefore, if µ(G) ≤ √ n, using their algorithm we can find the exact solution using a memory of sizeÕ(n).…”
Section: Preliminariesmentioning
confidence: 99%
“…In particular, our and Assadi et al [3]'s procedures are similar to the one in [11], which is aimed to for reducing space complexity of packing problems in streaming setting, but these conduct different analysis and provide different guarantees.…”
Section: Vertex Sparsification Lemmamentioning
confidence: 99%
“…The problem of MWM was also considered in other streaming models, such as the MapReduce model [8,15], the sliding-window model [8,9] and the turnstile stream model (allowing deletions as well as insertions) [1,5,7,14]. More general submodular-function matching problems in the semi-streaming model have been considered by Varadaraja and by Chakrabarti and Kale [6,18].…”
Section: Introductionmentioning
confidence: 99%